On Asymptotically Lacunary Statistical Equivalent Sequences of Order ? in Probability - Isik, Mahmut; Akbas, Kubra Elif (E D P Sciences, 2017)
In this study, we introduce and examine the concepts of asymptotically lacunary statistical equivalent of order alpha in probability and strong asymptotically lacunary equivalent of order alpha in probability. We give some relations connected to these concepts.
2nd International Conference on Computational Mathematics and Engineering Sciences (CMES) -- MAY 20-22, 2017 -- Istanbul, TURKEY
Keywords: Convergence; Summability